PENGARUH KEBIJAKAN DEVIDEN, KEBIJAKAN FINANCING, DAN BIAYA KEAGENAN TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perbankan yang Listing Bursa Efek Indonesia) - Mariatul Lutfia; Jeni Susyanti; M. Agus Salim (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to determine the effect of dividend policy, financing policy, and agency costs on company value partially or simultaneously. The population of this data is that banks listed on the Indonesia Stock Exchange in the 2015-2017 period amount to 43 banks. Sampling in this study with a purposive sampling technique of 10 banking samples. Analysis used using Multiple Linear Regression. The results of the analysis of this study show that dividend policy has no significant negative effect on firm value, financing policy has a significant negative effect on firm value, and agency costs have a negative and not significant effect on firm value. Keywords: Dividend Policy, Financing Policy, Agency Cost, Firm Value.